ANALYSIS OF STUDENTS MISCONCEPTIONS ABOUT REPRODUCTION IN PLANTS USING A FOUR-TIER DIAGNOSTIC TEST - Amelia, Mira; Thomas, Mary Margaret; Rusyati, Lillit (Universitas Tanjungpura, 2024)
Diagnosing students' conceptions is extremely valuable for assessing their level of understanding and preventing misconceptions. The four-tier test is a diagnostic instrument specifically designed to identify students' misconceptions, assess their grasp of concepts, and uncover confidence levels in their answers. Misconceptions refer to concepts that students comprehend but do not align with scientific understanding, Reproduction in plants is one of the subjects that can reveal misconceptions. yet students remain confident in their comprehension. Reproduction in plants is one of the subjects that can reveal misconceptions. To diagnose students' conceptions of plant reproduction, a set of four-tier multiple-choice questions was distributed to 101 9th-grade students who had previously studied the topic. Students' conceptions were classified into categories: scientific knowledge, false positives, false negatives, misconceptions, and lack of knowledge. Data analysis was conducted using MS Excel to calculate percentages and frequencies. The results demonstrate that students had a higher percentage of correct understanding compared to misconceptions. However, one particular subtopic, fertilization in plants and seed dispersal, exhibited the highest occurrence of misconceptions. This can be attributed to the students' overall strong scientific knowledge in these schools. To address identified misconceptions, teachers should establish connections between the material and real-life situations, engage students in projects and discussions, and openly discuss misconceptions. Additionally, introducing Latin terminology related to the subject matter can help familiarize students with the language used in the material. By implementing these strategies, teachers can effectively address misconceptions, promote a deeper understanding of plant reproduction, and provide meaningful learning experiences for students.